2016
DOI: 10.1111/1748-5967.12200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biosurfactants as insecticidal metabolites produced by Bacillus subtilis Y9

Abstract: Biosurfactants have been used for crop protection in integrated pest management programs, as they are generally biodegradable and environmentally friendly. While screening for insecticidal bacteria against green peach aphid, Myzus persicae, we found that a Bacillus isolate, Y9, exhibited strong surface tension activity and produced insecticidal metabolites. The insecticidal metabolites with surface tension activity were extracted from the cell‐free supernatant of Y9 and subjected to repetitive column chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…Bacterial endophytes have an advantage over bacteria inhabiting the rhizo- or phyllosphere, since living within a plant’s tissues represents an opportunity to be in constant “contact” with the plant’s cells, and endophytes become more integrated in plant metabolism than rhyzo- and phyllospheric microorganisms. PGPB strains show fungicidal ( Aydi Ben Abdallah et al, 2016 ), insecticidal ( Sorokan et al, 2016 ; Yang et al, 2017 ), and growth-promoting activities ( Sansinenea, 2019 ); synthesize antibiotics and biosurfactants ( Maksimov et al, 2020 ); and induce systemic resistance in plants against pathogens and pests ( Rashid and Chung, 2017 ). The entomopathogenic capacity of Bacillus thuringiensis strains to different orders of pests (Diptera, Lepidoptera, Hymenoptera, Coleoptera, Orthoptera, Hemiptera, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial endophytes have an advantage over bacteria inhabiting the rhizo- or phyllosphere, since living within a plant’s tissues represents an opportunity to be in constant “contact” with the plant’s cells, and endophytes become more integrated in plant metabolism than rhyzo- and phyllospheric microorganisms. PGPB strains show fungicidal ( Aydi Ben Abdallah et al, 2016 ), insecticidal ( Sorokan et al, 2016 ; Yang et al, 2017 ), and growth-promoting activities ( Sansinenea, 2019 ); synthesize antibiotics and biosurfactants ( Maksimov et al, 2020 ); and induce systemic resistance in plants against pathogens and pests ( Rashid and Chung, 2017 ). The entomopathogenic capacity of Bacillus thuringiensis strains to different orders of pests (Diptera, Lepidoptera, Hymenoptera, Coleoptera, Orthoptera, Hemiptera, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some surfactin-producing Bacillus strains can elicit ISR to Botrytis cinerea in grape, strawberry, and tomato plants [ 24 ] and Rhizoctonia solani in lettuce [ 25 ]. Recently, aphicidal and insecticidal activity of surfactin produced by B. subtilis and surfactin-producing strain B. subtilis 26D has been shown [ 13 , 14 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms with insecticidal activity were screened by mortality bioassays against M. persicae . Microbial cultures obtained as above were centrifuged at 12,000 x g for 20 min, and the resulting supernatant was used for bioassays as described earlier (Yang et al ). An isolate that exhibited the strongest insecticidal activity among the isolates was tested for the isolation of insecticidal metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…Biosurfactants should have diverse effects on aphids because they consist of a wide range of molecules, such as glycolipids, lipopeptides, polysaccharide–protein complexes, and lipids (Lang & Wagner ). Recently, biosurfactants were introduced as alternative agents for aphid control (Kim et al ; Yang et al ). Because biosurfactants are generally safer environmentally than other chemicals are, they are a potentially sustainable tool in pest management programs (Crombie ).…”
Section: Introductionmentioning
confidence: 99%